Implementation Of Restorative Justice Approach In Legal Protection Against Lightweight Crime By The Children - Rizky Adiyanzah Wicaksono; Sri Kusriyah Kusriyah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
Children who were doing mischief that led to the crime, should be against the law to account for his actions. Currently, prevention and control delinquency that resulted in minor criminal offenses is done through the implementation of the juvenile justice system to a restorative justice approach. The concept of restorative justice becomes a very important consideration in resolving criminal cases committed by children. The Supreme Court has issued a Supreme Court Regulation (Perma) No. 2 of 2012 on the Limitation Adjustment light crime and the amount of penalties in the Criminal Code, which essentially stipulates that the value limit losses in tipiring (Lightweight Crime) case is a maximum of 2.5 million, and against the threat case maximum criminal penalty of three months imprisonment or fine, as well as in the settlement tipiring must promote Restorative Justice. Child settlement, which is directed to resolving informally or out of court, with the involvement of all parties involved in the criminal act has occurred. Minor criminal offenses committed by children under the Act No. 11 of 2012 carried through the diversion mechanism by way of mediation or deliberation.Keywords: Restorative Justice; Lightweight Crime; Children.